The current research aims to reveal the relationship of academic stresses optimism –pessimism among students of the college of Physical Education and Sports Science, depending on the variables of sex (male, female) and class (second, third). - Subhi, Ali (Journal of Physical Education, 2016)
The current research aims to reveal the relationship of academic stresses optimism –pessimism among students of the college of Physical Education and Sports Science, depending on the variables of sex (male, female) and class (second, third).The achievement of the objectives of the current search requests from researcher found on theories that are associated research variables, as well as access to a range of previous studies and discussed as a prelude to complete the look as scientific right, with inclusion of the research community the current (1231) students, chose researcher them a stratified random sample by (125) students. The researcher has built tools to achieve the objectives of the research it is not available in the field of physical education: the measure of academic pressures and the measure of optimism and pessimism, reaching the stability of the pressure coefficient (0.92) Gronbach Alpha way, but optimism - pessimism scale has reached (0.78) in a way K.R.20 The number of paragraphs of the pressure gauge has reached (25) paragraph, and the measure of optimism - pessimism reached (18), the researcher appropriate statistical methods adopted to achieve the goals of the research.